Redefinition of the genus Silphitrombium (Trombidiformes: Neothrombiidae) with description of two new species parasitizing beetles (Coleoptera: Elateridae, Tenebrionidae) from Iran - Tashakor, Samaneh; Hajiqanbar, Hamidreza; Saboori, Alireza (Zootaxa, 2013)
Two new species of Silphitrombium Fain, 1992 (Acari: Prostigmata: Neothrombiidae), ectoparasites of beetles (Insecta: Coleoptera), are described from Sistan and Baluchestan Province, eastern Iran: S. elateridum sp. nov. on Heteroderes heideni Reitter, 1891 (Col.: Elateridae) and S. iranicum sp. nov. on Opatroides punctulatus Brullé, 1832 (Col.: Tenebrionidae) and the genus Silphitrombium is redefined. It is the first record of the relationship between beetles of the families Elateridae and Tenebrionidae, and mites of the genus Silphitrombium. A key to the species of the genus is presented.